2017
DOI: 10.1007/s11356-017-8775-1
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium adsorption, chelation and compartmentalization limit root-to-shoot translocation of cadmium in rice (Oryza sativa L.)

Abstract: Strategies to reduce cadmium (Cd) in rice grain, below concentrations that represent serious human health concerns, require that the mechanisms of Cd distribution and accumulation within rice plants be established. Here, a comprehensive hydroponic experiment was performed to investigate the differences in the Cd uptake, chelation and compartmentalization between high (D83B) and low (D62B) Cd-accumulation cultivars contrasting in Cd accumulation in order to establish the roles of these processes in limiting Cd … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(13 citation statements)
references
References 58 publications
1
12
0
Order By: Relevance
“…This tentative inference is in accord with previous elemental studies, which revealed signicant differences in the partitioning of Cd between plant organs for different cultivars of cacao, 7,30 and other crops. [26][27][28][29] Also notable is that the enrichment of light Cd isotopes in beans of the relatively pure Nacional cultivar (Tables 2 and 3) is in accord with observations made for Cd-tolerant and Cd accumulator plants, as these also revealed an enrichment of light Cd isotopes in stems and leaves relative to the hydroponic solution in which they were cultured. 62 The latter observation was thereby linked to the particular molecular mechanisms employed by these plants to cope with high levels of toxic Cd.…”
Section: Isotope Fractionation Between Cacao Beans and Leavessupporting
confidence: 83%
See 1 more Smart Citation
“…This tentative inference is in accord with previous elemental studies, which revealed signicant differences in the partitioning of Cd between plant organs for different cultivars of cacao, 7,30 and other crops. [26][27][28][29] Also notable is that the enrichment of light Cd isotopes in beans of the relatively pure Nacional cultivar (Tables 2 and 3) is in accord with observations made for Cd-tolerant and Cd accumulator plants, as these also revealed an enrichment of light Cd isotopes in stems and leaves relative to the hydroponic solution in which they were cultured. 62 The latter observation was thereby linked to the particular molecular mechanisms employed by these plants to cope with high levels of toxic Cd.…”
Section: Isotope Fractionation Between Cacao Beans and Leavessupporting
confidence: 83%
“…25 Previous studies on annual crops such as barley, potatoes and rice revealed clear cultivar-specic differences in Cd uptake and particularly root to shoot translocation, whereby the latter appears to be governed by the ability of plants to sequester Cd in roots with the aid of transporter proteins. [26][27][28][29] Two recent investigations on cacao also revealed cultivar-specic differences in Cd handling but with contrasting results. One study found that cultivars primarily differ in the efficiency of Cd translocation from shoots to beans, due to differences in the efficiency of Cd transfer from xylem to phloem.…”
Section: Introductionmentioning
confidence: 99%
“…However, the composite bacteria including B. subtilis and RP obviously reduced the concentration of Cd in rice grains. Presumably, B. subtilis partly formed spores for dormancy, while others rapidly consumed free oxygen in the soil environment, leading to local hypoxia . Paddy soil showed relatively anaerobic conditions when soaked with water .…”
Section: Discussionmentioning
confidence: 99%
“…Our study held that the accumulation amount of Cd and NPT were significantly positively correlated. The previous studies have shown that the GSH content in root for low-Cd rice varieties is higher than that for high-Cd rice cultivars [24]. Phytochelatin (PC), as a kind of NPT, plays an important role in the metastasis ability of Cd in rice cells.…”
Section: Discussionmentioning
confidence: 99%